2003
DOI: 10.2172/811192
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of NASA Lean Premixed Hydrogen Burner

Abstract: The stability characteristics of a prototype premixed, hydrogen-fueled burner were studied. The potential application is the use of hydrogen as a fuel for aircraft gas turbine operation. The burner configuration consisted of nine 6.72 mm (0.265 in) diameter channels through which the reactants entered the burner. Hydrogen was injected radially inward through two 0.906-mm (0.0357 in) diameter holes located on opposite sides of each air channel. In this way the region over which hydrogen and air were premixed wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…From the nature of the thick ceramic liners which held heat well, as the combustor was throttled down, it cooled slowly and it was difficult to determine the exact point of flame loss. Sandia 13 performed blowout tests for the NASA injector at ambient temperature and pressure and found that its characteristics were excellent (with blowout at equivalence ratios of 0.1). They did mixing studies, measurement OH, and stability the CH 4 , but did not measure the emissions of nitrogen oxides.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the nature of the thick ceramic liners which held heat well, as the combustor was throttled down, it cooled slowly and it was difficult to determine the exact point of flame loss. Sandia 13 performed blowout tests for the NASA injector at ambient temperature and pressure and found that its characteristics were excellent (with blowout at equivalence ratios of 0.1). They did mixing studies, measurement OH, and stability the CH 4 , but did not measure the emissions of nitrogen oxides.…”
Section: Resultsmentioning
confidence: 99%
“…11 Once the comparison was completed, the code was used to perform preliminary modeling of fuel injector concepts. 12 Work was also completed to examine the flame structure of a conceptual fuel nozzle at ambient conditions, 13 where data was collected using advanced laser diagnostic techniques which could then be used with computer code development and validation efforts. To date, several concepts utilizing lean direct LDI, lean pre-mixed, and hybrid combinations have been designed and tested, results of which are present herein.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Fig. 1 shows a hydrogen flame in a burner that has been studied in collaboration with NASA Glenn [7]. The conditions shown are premixed hydrogen and air at an equivalence ratio, φ, of 0.33 and an inlet velocity of 90 m/s.…”
Section: Introductionmentioning
confidence: 99%